Conjunctiva granuloma, a rare presentation of ocular leptospirosis presenting as conjunctiva granuloma : case series - Yeoh, Shao Yin; Anhar HS,; Chua, SM; Nor FAJ,; Raja NRO,; Azida JWAK, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Diagnosis of ocular leptospirosis is challenging and requires a high index of suspicion of previous leptospiral infection and good laboratory support. This case series focuses on two young females with unilateral conjunctiva granuloma. To the best of our knowledge, these are the first two cases of ocular leptospirosis with conjunctiva granuloma. The definitive diagnosis of ocular leptospirosis was based on laboratory studies in which conjunctival biopsies in these two cases showed positive leptospira DNA. Retrospectively, the history was suggestive as both patients had exposure to leptospira organism. In conclusion, a diagnosis of ocular leptospirosis requires a high clinical suspicion index supported by mandatory laboratory investigations.